Spiritual Yarning: Craft-making as Getting Along in Everyday Life - Myllys, Riikka (Journal of religion in Europe, 2020)
This article investigates how spirituality relates to craft-making. Spirituality is understood to have both religious and nonreligious content depending on the person. The data was collected in a one-year period of observation and interviews. The results show that spirituality related to craft-making may be both religious and nonreligious. It is noteworthy, however, that religious and nonreligious spirituality are related to different aspects of craft-making: the social and prosocial aspects of craft-making are mostly religiously spiritual, whereas individually centred aspects are not. Altogether, the spirituality of craft-making is largely immanent and wellbeing-oriented. As such, its focus is on getting along in everyday life.